Analysis of Lumbar Foramina Size Change in Patients with Lumbar Spondylolisthesis using Kinetic Magnetic Resonance Imaging. Issue 1 (April 2016) - Huang, Hsiang-Ming; Yang, Jui-Jung; Patel, Neil; Wang, Justin; Hsieh, Patrick; Liu, John; Buser, Zorica; Wang, Jeffrey C.
Introduction: The pathology of lumbar spondylolisthesis contributes to lumbar instability and significant clinical symptoms. However, the effect on intervertebral foraminal area (FA) during motion change is not well understood. Material and Methods: In this study we used 107 patients diagnosed with single or multiple level lumbar spondylolisthesis at L3–L4, L4–L5 or L5–S1. All patients were initially divided into two groups: group A (sliding percentage 0–3%) and group B (sliding percentage ≥4%). Sliding percentage and FA size in neutral, flexion and extension were measured using kMRI. The FA change in different sliding groups at L5-S1 level was further analyzed. Results: The number of patients in the group A (sliding percentage 1–3%) was 68 at L3–4, 38 at L4–5 and 32 at L5-S1 spine levels. The number of patients in the group B (sliding percentage ≥4%) was the following: 39 at L3–L4, 69 at L4–L5 and 75 at L5–S1. The mean FA in both groups changed with different spine positions. When considering all levels, the average FA increased 17% from neutral to flexion and decreased 21% from neutral to extension. Similarly, there was a significant difference in FA in flexion at L5-S1 ( p < 0.004) between the groups. For L5/S1 patients, 104 patients were divided into three sub-groups according to the sliding percentage (group I (0–9%), group II (10–19%) and group III (20–29%)). The FA was significantly increased in the flexion position and decreased in the extension position in all three groups. In group III FA size was significantly decreased from neutral to flexion when compared with Group I ( p < 0.022). The FA size was significantly increased from neutral to extension when group III was compared with groups I and II ( p < 0.000 and p < 0.017, respectively). Conclusion: Our kMRI study revealed position-dependent changes of the intervertebral foramen. In patients with severe sagittal subluxation the change in FA from neutral to extension position demonstrated the largest decrease. This change may also correlate with changes in neuroforaminal stenosis and nerve root compression and its associated symptoms and should be taken in consideration when choosing the treatment option.